The shortest day - Cooper, Susan, 1935- (Candlewick Press, 2019)
"A celebration of the winter solstice and the Yuletide season. As the sun set on the shortest day of the year, early people would gather to prepare for the long night ahead. They built fires and lit candles. They played music, bringing their own light to the darkness, while wondering if the sun would ever rise again"--